Virtual screening for high affinity guests for synthetic supramolecular receptors1. Issue 5 (20th May 2015) - Cullen, William; Turega, Simon; Hunter, Christopher A.; Ward, Michael D.
<x xml:space="preserve">Abstract</x> The protein/ligand docking programme 'GOLD' can be used to identify new strongly-binding guests for a synthetic coordination cage host.